A new genus and new species of Edessinae (Hemiptera: Heteroptera: Pentatomidae) - Almeida, Flavio Roberto De Albuquerque; Nunes, Benedito Mendes; Fernandes, Jose Antonio Marin (Zootaxa, 2018)
The genus Plagaedessa gen. n. is proposed to accommodate four species: Edessa celsa Distant and three new species: P. distanti sp. n., P. nigrovittata sp. n. and P. maranhensis sp. n. The new genus is characterized by the antennae black with the antennomer I showing a yellow spot on ventral surface, legs yellow with femora and tibiae showing two or three longitudinal black stripes, gonapophysis 9 with a sclerotized area bearing a protuberance close to gonocoxites 9 and pygophore with black posterolateral angles strongly developed. Diagnosis, illustrations of the metasternal process and external and internal genitalia, photographs of the dorsal and ventral view, and a distribution map are provided. A key to the genera of Edessinae and subgenera of Edessa, and a key to the species of Plagaedessa are also provided. Male and female genitalia of Plagaedessa celsa n. comb. are described for the first time. Distribution of P. celsa is extended to Costa Rica and Mexico. The lectotype of Edessa celsa is here designated.